Predictors and correlates of sexual avoidance among partnered older adults among Norway, Denmark, Belgium, and Portugal - Carvalheira, Ana (2019)
Research on sex in later life has been concerned with documenting that older people continue to have sex and establishing the links between good health and sexual activity. Although sexual avoidance is common in clinical and nonclinical populations of older adults, little attention has been given to the motives for sexual avoidance. To address gaps in the literature on sexual avoidance, the present study explored the self-reported reasons for, and correlates of, sexual avoidance in older partnered individuals with probability samples of 60–75-year-olds in four European countries (Norway, Denmark, Belgium, and Portugal). Results revealed significant differences between men and women in sexual avoidance, with women reporting more avoidance than men. The main reasons reported for avoiding sex were sexual difficulties, health problems, partner’s sexual difficulties, and lack of sexual interest. Among men, significant predictors of sexual avoidance were age, relationship intimacy (the only relational predictor), physical health, and own and partner’s sexual problems. In women, significant predictors of sexual avoidance were age, relationship duration, relationship satisfaction, relationship intimacy, physical and mental health, and own and partner’s sexual problems. Thus, in men, health-related factors were more important predictors of sexual avoidance than relationship factors. In women, relationship factors were as important as health-related factors. These findings provide insight into an under-researched area. They also have important implications for health care and could inform the development of tailored sexual health interventions in older adults. Keywords Older adults · Sexual avoidance · Relationship intimacy · Relationship